Physiological basis of dietary prevention of perimenopausal disorders in the context of dietary habits associated with the consumption of water and beverages by women aged 45-65 - Sadowska, Joanna; Remiszewska, Zuzanna (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction : This study aimed to evaluate the amount of water and type of beverages consumed by women of perimenopausal age against a background of dietary prevention of perimenopausal disorders. Material and methods : This study was conducted in autumn 2012, in Wielkopolska Province (Poland), on 100 women aged from 45 to 65 years, employed as office workers. Information on the diet, beverages consumption and anthropometric data were collected. Results : Analysis of the nutritional status of the surveyed women showed that over 50% of them had excess body weight. Analysis of the survey results indicated that the amount of water in the diet of the examined women was appropriate, although the type of drinks consumed was inadequate. The women consumed too much coffee and tea, and simultaneously had a low intake of potable water. More than a half of the surveyed women sweetened coffee and tea. Women with excess body weight did so statistically significantly quite often, and they also used larger amounts of sugar for sweetening. Nearly 60% of the surveyed women added milk, or less frequently cream, to coffee. Milk was statistically significantly more frequently chosen by women with normal body weight, and cream by women with excess body weight. There was a positive correlation between body mass index and the energy value of the consumed fluids. Conclusions : The dietary irregularities identified in this study may intensify perimenopausal symptoms and contribute to the development of diet-related chronic diseases. Taking into account the observed irregularities, it seems appropriate to provide perimenopausal women with nutrition education and diet correction, including the amount and type of fluids consumed.